Lyapunov stability solutions of fractional integrodifferential equations. (30th September 2004) - Momani, Shaher; Hadid, Samir
Abstract : Lyapunov stability and asymptotic stability conditions for the solutions of the fractional integrodiffrential equationsx ( α ) ( t ) = f ( t, x ( t ) ) + ∫ t 0 t k ( t, s, x ( s ) ) d s, 0 < α ≤ 1, with the initial conditionx ( α − 1 ) ( t 0 ) = x 0, have been investigated. Our methods are applications of Gronwall's lemma and Schwartz inequality.